Biology of fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) on maize - Dileepkumar, N T; Muralimohan, K (Indian Journal of Plant Protection, 2022)
Fall armyworm, Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae) is a new invasive species in India. Fall armyworm is known for polyphagous behaviour and feeds on 353 plant species belonging to 76 families (Montezano et al., 2018) including maize, rice, sorghum, sugarcane, cabbage, beet, peanut, soybean, alfalfa, onion, tomato, potato and cotton (Pogue, 2002; Anonymous, 2016) and causes significant loss in crop production. It is native to the Americas and found in most parts of the Western Hemisphere, from southern Canada to Chile and Argentina. Of late, the fall armyworm was noticed in West Africa and East Africa during 2016 and 2017, respectively and currently, it is damaging crops in over 20 African countries (Goergen et al., 2016; Abrahams et al., 2017; Cock et al., 2017). In Brazil, fall armyworm caused up to 34% reduction in maize grain yield that amounted to an annual loss of US 400 million (Lima et al., 2010). Yield losses in maize reached up to 32 % in the United States (Wiseman and Isenhour, 1993) and 45-60 % in Nicaragua (Hruska and Glandstone, 1988). In India, a quick roving survey at Karnataka suggested that fall armyworm could cause a damage ranging from 9 to 62.5 % on maize